1999
DOI: 10.1088/0952-4746/19/2/304
|View full text |Cite
|
Sign up to set email alerts
|

A gamma camera for measurements of internal contamination after a radiological accident

Abstract: After a radiological accident with the release of large amounts of radionuclides into the environment, measurements of the external and internal exposure of the public will be urgently required. The aim of this study was to investigate the properties of a gamma camera with regard to measurements of internal contamination. The gamma camera was used as a detector without any imaging function. The lowest minimum detectable activity, 100 Bq 131I in thyroid measured over the neck and 400 Bq 137Cs in the whole body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The derived calibration factors and MDAs for 137 Cs and 60 Co showed good agreement with previous studies [6,[8][9][10], but it is important to bear in mind that different gamma camera models, energy windows, settings, phantoms and calibration geometries are used in different studies, which makes direct comparisons difficult. To the best of our knowledge, 152 Eu and 40 K have not been previously studied in this situation.…”
Section: Validation and Comparison With Previous Studiessupporting
confidence: 80%
See 4 more Smart Citations
“…The derived calibration factors and MDAs for 137 Cs and 60 Co showed good agreement with previous studies [6,[8][9][10], but it is important to bear in mind that different gamma camera models, energy windows, settings, phantoms and calibration geometries are used in different studies, which makes direct comparisons difficult. To the best of our knowledge, 152 Eu and 40 K have not been previously studied in this situation.…”
Section: Validation and Comparison With Previous Studiessupporting
confidence: 80%
“…The detector heads can rotate 360 • around the patient table and are usually located 180 • relative to each other. Several studies have shown that the detection efficiency can be enhanced by removing the collimators normally used to enable visualization of the radionuclide distribution [6][7][8]. In this study, we were only interested in the quantification of radionuclides and, therefore, all measurements were performed without the collimators, leaving only a thin (0.5 cm) Plexiglas plate to protect the crystal from damage and contamination, the so-called intrinsic mode.…”
Section: Gamma Camera Systemsmentioning
confidence: 99%
See 3 more Smart Citations